Status of seagrass species and distribution in Peninsular Malaysia - Zakaria, Muta Harah; Bujang, Japar Sidik; Che Alias, Muhammad Afif; Syed, Nurul Nur Farahin; Ramaiya, Shiamala Devi (2023)
Seagrasses are the only flowering plants that have adapted to live in marine and estuarine habitats and are submerged most of the time. Sixteen species of seagrasses in Malaysia comprising Enhalus acoroides, Thalassia hemprichii, Halophila beccarii, Halophila decipiens, Halophila ovalis, Halophila major, Halophila minor, Halophila spinulosa, Halophila tricostata, Halodule pinifolia, Halodule uninervis, Cymodocea rotundata, Cymodocea serrulata, Syringodium isoetifolium, Thalassodendron ciliatum, and Ruppia maritima. They occur at 146 sites, 76 sites in Peninsular Malaysia, 60 sites in Sabah, and ten in Sarawak. The seagrass communities are site-specific and have distinct species assemblages ranging from monospecific beds and beds of two species to seagrass beds with mixed species in waters of the offshore islands with fringing coral reefs and sub-tidal shoals. In Peninsular Malaysia, 14 seagrass species occurrence is characterized by variations in the habitats that are accessible and the dominant environmental factors along the west and east coastlines. On the west coast, seagrasses occur in shallow coastal waters, mainly in sheltered stretches of sandy-to-sandy mud intertidal open coast, rocky shores, coral reef platforms, sandy to mudflats, and mudflats of mangroves in the south. Seagrasses are in the east coast's semi-enclosed lagoons and sandy mud intertidal areas. Seagrass beds provide multiple benefits, e.g., ecological functions, sources of food, and an important reservoir of coastal biodiversity, yet they are continually facing losses and threatened by human activities. This study provides information on the current seagrass distribution and status assessment, particularly highlighting losses and various threats of seagrasses in Peninsular Malaysia. We hope this information can be the basis or initiatives for protecting and conserving seagrass ecosystems within protected areas and outside their boundaries.